The Effect of Wordwall Media with Interactive Boards on Students’ Learning Outcomes in the Classification of Living Things - Azura, Dedek; Khairuna, Khairuna (Journal of Educational Sciences, 2025)
This study aims to examine the effect of using wordwall interactive board-based media on student learning outcomes in the subject of classification of living things. The study used a quasi-experimental design with two groups, namely an experimental class that used interactive wordwall media and a control class that applied conventional learning methods. The research subjects consisted of 64 students who were divided evenly into two classes, 32 students in each class. The research instrument was a multiple-choice test administered at the pretest and post-test stages. The data were analyzed using an independent t-test after fulfilling the assumptions of normality and homogeneity. The results showed that the average post-test score of the experimental class (86.67) was higher than that of the control class (71.67). The independent t-test produced a t-value of 6.073 with a significance of 0.000 (< 0.05), indicating a significant difference between the two groups. Thus, it can be concluded that the use of interactive wordwall media contributes positively to improving student learning outcomes.